Receptor/Raft Ratio Is a Determinant for LRP6 Phosphorylation and WNT/β-Catenin Signaling - Haack, Fiete; Köster, Till; Uhrmacher, Adelinde M. (Frontiers in Cell and Developmental Biology, 2021)
Microdomains or lipid rafts greatly affect the distribution of proteins and peptides in the membrane and play a vital role in the formation and activation of receptor/protein complexes. A prominent example for the decisive impact of lipid rafts on signaling is LRP6, whose localization to the same lipid rafts domain as the kinase CK1y is crucial for its successful phosphorylation and the subsequent activation of the signalosome, hence WNT/beta-catenin signaling. However, according to various experimental measurements, approximately 25-35% of the cell plasma membrane is covered by nanoscopic raft domains with diameters ranging between 50 - 100 nm. Translating these values to the membrane of a "normal sized" cell yields a raft abundance, that, by far, outnumbers the membrane-associated pathway components of most individual signaling pathway, such as receptor and kinases. To analyze whether and how the quantitative ratio between receptor and rafts affects LRP6 phosphorylation and WNT/beta-catenin pathway activation, we present a computational modeling study, that for the first time employs realistic raft numbers in a compartment-based pathway model. Our simulation experiments indicate, that for receptor/raft ratios smaller than 1, i.e. when the raft number clearly exceeds the number of pathway specific membrane proteins, we observe significant decrease in LRP6 phosphorylation and downstream pathway activity. Our results suggest that pathway specific targeting and sorting mechanism are required to significantly narrow down the receptor/raft ratio and to enable the formation of the LRP6 signalosome, hence signalling.